GENETIC VARIABILITY FOR YIELD PARAMETERS AND RUST RESISTANCE IN F2 POPULATION OF WHEAT (TRITICUM AESTIVUM L.) - ARATI YADAWAD; R. R. HANCHINAL; H. L. NADAF; S. A. DESAI; SUMA BIRADAR; V. RUDRA NAIK (The Bioscan, 2015)
The aim of this study was to estimate the extent of genetic variability for grain yield, its component traits and leaf rust resistance in F2 population of the cross DWR162 X PBW343. High Phenotypic Coefficient of Variation (PCV) and Genotypic Coefficient of Variation (GCV) were observed for all the characters except for days to fifty percent flowering, spike length and number of spikelet’s per spike. High heritability and genetic advance were recorded for all the characters except days to fifty percent flowering, spike length and number of spikelet’s per spike. This suggested better scope for selecting superior transgressive segregants in this population. For leaf rust incidence, high genetic coefficients of variation along with high heritability and genetic advance were recorded indicating the greater effectiveness of selection and improvement can be expected for leaf rust resistance. Present investigation suggests that selection in F2 population of DWR162 X PBW343 will be effective in selecting superior plants for yield parameters and leaf rust resistance in evolving high yielding leaf rust resistant genotype in wheat.